ON THE ISSUE OF COMMUNICATIVE CONDITIONS FOR EDUCATIONAL CHANGES - A. A. POLONNIKOV (Высшее образование в России)
The article focuses on a communicative ritual, which is considered to be one of the causes for blocking education transformations. It is assumed that ritual communication is based on a restricted linguistic code that provides a reproduction of the current didactic relationships. A hypothesis is put forward, according to which their changes are due to the appearance of an extended linguistic code in the learning communication. Addressing an extended encoding will enable the participants of learning to make a communicative ritual problematic, as well as to act in the capacity of subjects capable of designing and developing didactic conditions. A code change is understood as the change of the means creating individuals’ education reality.